29-36 Warrenton Street, June 2, 1930 - Boston Traveler (Tufts Archival Research Center, 2005)
Street-level view looking southwest down Warrenton Street toward Shawmut Avenue. The image is of the facades on the west side of the street. The Liberty Hotel is in the center of the image. A pedestrian is looking at the sidewalk. On verso is a newspaper clipping which reads, view in front of the Liberty Hotel, Warrenton Street, where two alleged bootleggers were shot down by machine-gun fire early today. The point where the victims fell is marked by the man in the foreground. 9 5/8 x 7 5/8 overall 10 x 8 Photographs